THE DIVERSITY OF LIFE CYCLES AND THEIR ROLE IN THE EVOLUTION OF BASIC CHROMOSOME NUMBERS IN VARIOUS ORGANISMS - A. I. Shchapova (Вавиловский журнал генетики и селекции, 2014)
Basic chromosome numbers are compared among species of four gymnosperm divisions, three Anthophyta families, and three Mammalia subclasses, with different life cycle types. Gymnosperm and angiosperm species characterized by alternation of haploid and diploid phases, sporic meiotic reduction, hermaphroditism, and sporophyte predominance have small basic chromosome numbers (BCNs): x = 7 to 14, and most of their species are polyploids. Species of various mammal subclasses, with sporophyte predominance gametic meiotic reduction, dioecious, and characterized by a chromosomal sex-determination system broadly vary in BCN. Monotremata species (oviparous) have small BCNs and ploidy levels 10x. The BCN variability among marsupials is x = 5 to 16, and in Euarchontoglires (placentals) x = 3 to 51. No polyploids have been found among marsupials or placentals.Data on chromosome banding and various kinds of fluorescence hybridization of chromosome-specific probes indicate that the BCN evolution in angiosperms was accompanied by repeated crosses and polyploidization of species with few chromosomes followed by dysploidization by means of conjugation of nonhomologous chromosomes and reciprocal translocations. It is believed that the BCN of the placental ancestor was x = 40–50; of the marsupial ancestor, 16–20; and of oviparous mammals, 5–6. The significant difference among BCNs of the ancestors of the three mammal subclasses, which diverged tens of millions of years ago, suggests that the evolution of BCNS in the ancestors of marsupials and placentals involved polyploidy followed by dysploidy.The species analyzed demonstrate a correlation between life cycle type and BCN.The results indicate that the genetic difference in sex determination systems were the main cause of BCN variation in the species analyzed, differing in life cycle type. The lengths of the haploid and diploid phases are of minor significance.